Factors that influence women's decision on infant feeding: An integrative review. Issue 5 (September 2022) - Matriano, Marie Gabrielle; Ivers, Rowena; Meedya, Shahla
Abstract: Background: Many women stop breastfeeding earlier than what they intended prior to birth. Although there are many studies that focus on the factors that influence women's antenatal breastfeeding decisions, the factors that influence women's decisions during the continuum of antenatal and postnatal period are less known. Aim: To understand and synthesise the contemporary factors that influence women's decisions on infant feeding from the antenatal period and across the breastfeeding continuum. Method: Five online databases (CINAHL, Medline, PubMed, Scopus and Web of Science) were searched. We included original search articles that were published since 2015 to August 2021 and were available in English. The framework of Whittemore and Knafl was used to guide this integrative literature review. Out of the 872 articles identified, 14 studies met the inclusion criteria of our study. We used theory of birth territory and midwifery guardianship to synthesise the interactions between the themes. Findings: Five main themes were identified: (a) Women's own views, (b) Family and friend's preferences and advice, (c) Health professional's preference, advice and practice, (d) Sociocultural norms, and (e) Media representation . The interaction between the themes was explained based on women's intrinsic and extrinsic power outlined in the birth territory and midwifery guardianship theory. Conclusion: The factors that influence women's decisions towards infant feeding methods are complex and multi-dimensional. Promoting and supporting women towards breastfeeding need to focus on the factors that are tailored for a woman within her social network where she can feel safe about her breastfeeding decisions.